2015
DOI: 10.1007/s00216-015-9119-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of d-serine in human serum by LC-MS/MS using a triazole-bonded column after pre-column derivatization with (S)-4-(3-isothiocyanatopyrrolidin-1-yl)-7- (N, N-dimethylaminosulfonyl)-2,1,3-benzoxadiazole

Abstract: An LC-MS/MS-based method for determining D-serine (Ser), an endogenous co-agonist of the N-methyl-D-aspartate receptor, in human serum, was developed and validated using a triazole-bonded silica-packed column after pre-column fluorescence derivatization with a chiral labeling reagent, (S)-4-(3-isothiocyanatopyrrolidin-1-yl)-7-(N,N-dimethylaminosulfonyl)-2,1,3-benzoxadiazole. Enantiomeric separation of the D- and L-Ser derivatives occurred in the triazole-bonded column (R s: 1.85) with CH3CN/100 mM HCO2NH4 in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We recently reported a unique retention phenomenon, whereby the temperature of a triazole-bonded column considerably affected the retention behaviour of (S)-DBD-PyNCS-D, L-serine (Sakamoto et al, 2016). In the previous study, an increase in column temperature led to an increased capacity factor (k) of (S)-DBD-PyNCS-D,L-serine.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We recently reported a unique retention phenomenon, whereby the temperature of a triazole-bonded column considerably affected the retention behaviour of (S)-DBD-PyNCS-D, L-serine (Sakamoto et al, 2016). In the previous study, an increase in column temperature led to an increased capacity factor (k) of (S)-DBD-PyNCS-D,L-serine.…”
Section: Resultsmentioning
confidence: 98%
“…triazole-bonded silica packed column (Cosmosil HILIC®), after derivatization with (S)-DBD-PyNCS. Using the LC-MS/MS method, the enantiomeric separation and highly sensitive detection of both serine enantiomers in human serum were successfully achieved (Sakamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that augmentation of the triazole‐bonded column temperature leads to an increased capacity factor ( k ) and ion intensity of ( R )‐DBD‐PyNCS‐ l ‐Trp and ‐ l ‐KYN . We also recently reported that the simultaneous determination of both endogenous d ‐ and l ‐serine in human serum was achieved by liquid chromatography (LC)‐MS/MS using a triazole‐bonded column after derivatization of the d ‐ and l ‐serine with ( S )‐DBD‐PyNCS . In this study, it was found that the d ‐enantiomer eluted earlier than the l ‐enantiomer of serine using ( S )‐DBD‐PyNCS on the triazole‐bonded column.…”
Section: Introductionmentioning
confidence: 69%
“…D‐Ser is abundant in the forebrain and function zone as a co‐agonist of NMDA receptors to enhance neurotransmission . Decreased D‐Ser levels in the plasma or serum have been reported in clinical studies of schizophrenia patients . Plasma concentrations of D‐serine and the ratio of D‐serine to total serine may be used as clinically translatable biomarkers in NMDA receptor‐related disease .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Decreased D-Ser levels in the plasma or serum have been reported in clinical studies of schizophrenia patients. 17,18 Plasma concentrations of D-serine and the ratio of D-serine to total serine may be used as clinically translatable biomarkers in NMDA receptorrelated disease. 19 D-amino acid has been gradually accepted as a new target molecule due to its physiological effect.…”
Section: Introductionmentioning
confidence: 99%